Dishonest Behavior: From Theory to Practice - Dan Ariely (Frontiers Research Topics, 2016)
The rapidly growing field of behavioral ethics shows that dishonest acts are highly prevalent in all walks of life, from corruption among politicians through flagrant cases of doping in sports, to everyday slips and misdemeanors of ordinary people who nevertheless perceive themselves as highly moral. When considered cumulatively, these seemingly innocuous and ordinary unethical behaviors cause considerable societal damage and add up to billions of dollars annually. Research in behavioral ethics has made tremendous advances in characterizing many contextual and social factors that promote or hinder dishonesty. These findings have prompted the development of interventions to curb dishonesty and to help individuals become more committed to ethical standards. The current e-book includes studies that test and advance current theory and deepen our understanding of the cognitive and physiological processes underlying dishonest behavior, discuss possible implications of findings in behavioral ethics research for real life situations, document dishonest behavior in the field and/or directly examines interventions to reduce it.